Penerapan Model Pembelajaran Langsung Untuk Meningkatkan Kreativitas Anak Sekolah Dasar - Dewi Widiana Rahayu (International Consortium of Education and Culture Research Studies, 2018)
This research uses classroom action research with Kemmis & Taggart model. This research uses 4 stages including, planning, implementation of action, observation and reflection. Research conducted in SDN Randegansari Driyorejo District Gresik Regency aims to determine the development of student creativity in decorative motif material. The data of teacher and student activity is obtained through observation. The results showed that the implementation of dye binding technique on ornamental motif material can improve the creativity of students with the average about 65,5 or 45,5% in cycle I, 68,7 0r 87,09% in cycle II, and 80,6 or 93,5% in cycle III.. The results of this study indicate that creativity can be improved by implementing dye binding techniques so that students' creative attitude in the learning process can develop and student creativity increases.